2020
DOI: 10.1016/j.cub.2019.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Single-Neuron Representations of Spatial Targets in Humans

Abstract: Highlights d Epilepsy patients performed a spatial navigation task during single-neuron recordings d Neuronal firing in the medial temporal lobe represents spatial target locations d Single-neuron activity does not represent the subject's own location in this task d Neuronal activity also varied with heading direction and order of navigation periods

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 66 publications
13
49
0
Order By: Relevance
“…3K) their firing rates in association with good memory performance. The finding of both positive and negative memory-sensitive cells is in 130 line with previous human single-neuron recordings (20), and negative memory-sensitive cells may be related to inhibitory engrams (21). We observed that memory-related firing rate changes were common among anchor cells (17 of 58 anchor cells were memory-sensitive cells; chi-squared test, χ²=11.709, P<0.001), but not among direction, place, or other cells (all χ²<1.717, all P>0.190; Fig.…”
Section: Main Textsupporting
confidence: 90%
See 3 more Smart Citations
“…3K) their firing rates in association with good memory performance. The finding of both positive and negative memory-sensitive cells is in 130 line with previous human single-neuron recordings (20), and negative memory-sensitive cells may be related to inhibitory engrams (21). We observed that memory-related firing rate changes were common among anchor cells (17 of 58 anchor cells were memory-sensitive cells; chi-squared test, χ²=11.709, P<0.001), but not among direction, place, or other cells (all χ²<1.717, all P>0.190; Fig.…”
Section: Main Textsupporting
confidence: 90%
“…For example, head-direction cells in rodents often exhibit baseline firing rates of about 0 spikes/s and increase their firing rates up to about 100 spikes/s at the preferred head direction (3). Directionally sensitive neurons in our study showed only moderate firing rate increases when subjects moved in the preferred direction [for similar tuning strengths, see, 710 e.g., (2,20,24,43)]. Thus, the use of the classical terminology (e.g., the term "place cells" to refer to spatially modulated neurons) should be treated with caution (we adhere to these terms for ease of reading).…”
Section: Supplementary Textmentioning
confidence: 67%
See 2 more Smart Citations
“…We developed AR and VR paradigms that adapted the "Treasure Hunt" spatial memory task, previously used in [17,18,20,31]. Treasure Hunt is an object-location associative memory task in which subjects are asked to remember the locations of various hidden objects in a virtual environment.…”
Section: Methodsmentioning
confidence: 99%